Yellow Pumpkin Fruit Extract (Cucurbita moschata D) in Cream Preparation as a Facial Moisturizer - Fauzia, Rizki Rahmah; Nafi'ah, Rahma; Widyaningsih, Hanum (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Indonesia is a tropical country that has a fairly high exposure to sunlight, but excessive sun exposure can cause skin damage such as dry skin with prevalence of 41,2% to 99,1% in the elderly adult population . Therefore, it is necessary to make products that function to moisturize the skin. Yellow pumpkin is an alternative ingredient that can be used as a skin moisturizer because it contains flavonoid compounds, tannins, saponins, alkaloids, and triterpenoids. The novelty in this study is that no one has researched yellow pumpkin fruit extract cream as a facial moisturizer, different measurement methods, substitution of ingredients in the formula from VCO to MCT and the addition of preservatives and fragrances. This study aims to determine the effectiveness of facial moisturizers, yellow pumpkin fruit extract creams, and the physical quality of preparations. In this study, the researcher used an experimental method. The extraction process uses a maceration method with a solvent of 96%, then a cream formula is made with a concentration of yellow pumpkin fruit extract of 5%, 10%, and 15%. The evaluation of facial moisturizing cream preparations includes organoleptis tests, homogeneity tests, pH tests, dispersion tests, adhesion tests, viscosity tests, and irritation tests. The tool used to measure skin moisture is Skin Analyzer CR-302 by looking at the percentage of moisture. The results of the effectiveness test of yellow pumpkin extract facial moisturizing cream (Cucurbita moschata D) for 28 days of use had a moisture percentage of 44.00% at an extract concentration of 5%, 48.67% at an extract concentration of 10%, and 55.00% at an extract concentration of 15%. The higher the concentration of the extract, the better the moisture level. The results of the effectiveness test of yellow pumpkin fruit extract cream preparations (Cucurbita moschata D) have effectiveness as a skin moisturizer with a sig value (0.008 0.050). The conclusion showed that the preparation of the moisturizing cream of yellow pumpkin fruit extract (Cucurbita moschata D) with the best concentration at a concentration of 15%. The preparation of the moisturizing cream of yellow pumpkin fruit extract (Cucurbita moschata D) meets the requirements of the evaluation test.